2017
DOI: 10.3389/fnut.2017.00012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity of the Gastric Content of Preterm Infants during Their First Month of Life at the Hospital

Abstract: Studies focused on the stomach microbiota are relatively scarce, and most of them are focused on the adult population. The aim of this work is to describe the bacterial communities inhabiting the gastric content (GC) of preterm neonates. For that purpose, GC samples were collected weekly from a total of 13 preterm neonates during their first month of life within their hospital stay. Samples were analyzed by using both culture-dependent and -independent techniques. The former allowed the isolation of bacteria b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…Moreover, the mode of breastfeeding (direct breastfeeding and indirect breastfeeding) could be assumed as a cause of more diverse meconium microbiota in exclusive breastfeeding (EBF) neonates. Enterobacteriaceae and potential pathogens were shown to be enriched with indirect breastfeeding, consistent with culture-dependent studies where pump expression increased the abundance of Enterobacteriaceae and other Gram-negative bacteria in milk [ 25 , 26 ]. However, another study has found no significant differences in gut microbial communities between EBF and non-EBF infants [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, the mode of breastfeeding (direct breastfeeding and indirect breastfeeding) could be assumed as a cause of more diverse meconium microbiota in exclusive breastfeeding (EBF) neonates. Enterobacteriaceae and potential pathogens were shown to be enriched with indirect breastfeeding, consistent with culture-dependent studies where pump expression increased the abundance of Enterobacteriaceae and other Gram-negative bacteria in milk [ 25 , 26 ]. However, another study has found no significant differences in gut microbial communities between EBF and non-EBF infants [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Serratia is one of the major bacteria in the stomach of H. pylori -negative individuals ( Li et al, 2017 ). Serratia is reported to be the most abundant genera in the gastric microbiota of both preterm infants and formula milk-fed infants with a median relative abundance of 15.68% and 34.20%, respectively ( Moles et al, 2017 ; Ku et al, 2020 ). Serratia is often found in the living environment (children’s toys) and pathological conditions (blood infections, skin abscesses, bacterial meningitis, et al) ( Martín-Nalda et al, 2011 ; Abdinia et al, 2014 ; Martínez-Bastidas et al, 2014 ; Johnson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different milk types were subsequently administered through enteral feeding tubes which are well-suited devices for the growth and enrichment of high risk hospital-associated clones, which subsequently act as reservoirs of such clones [28,[50][51][52]. In preterm neonates, gastric pH values are closer to neutrality while the pylorus is more relaxed than in adults; this allows the entry of gut bacteria to the gastric compartment.…”
Section: Discussionmentioning
confidence: 99%